Предмет: Алгебра,
автор: Mangik
Решите уравнение:
2(x+2)(x-1)=(1-2x)(3-x)
Ответы
Автор ответа:
0
=(2х+4)(х-1)=(1-2х)(3-х)= 2х^2-2х+4х-4=3-х-6x+2х^2= 9х-7
Автор ответа:
0
2 (х^2-х+2х-2)=3-х-6х+2х^2;;;;;;;;;; 2х^2-2х+4х-4=3-х-6х+2х^2;;;;;;;;;;2х^2-2х+4х+х+6х-2х^2=4+3;;;;;;;;; 9х=7;;;;;х=7/9
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Математика,
автор: skarimjonov
Предмет: Физкультура и спорт,
автор: adiaaogncgio
Предмет: Математика,
автор: kkyykkii21212121
Предмет: Физика,
автор: Evgeeniaaa
Предмет: Алгебра,
автор: алианааааааааааа